Tourism and hospitality firms' response to COVID-19: the role of entrepreneurial orientation and managers' market recovery perception - Maria de Lurdes Calisto; Teresa Costa; Jorge Umbelino (Cogent Business & Management, 2024)
Literature is prolific on how several crises have affected tourism and hospitality. However, those studies are primarily concerned with the impacts at the destination level and less with tourism businesses' resilience and recovery. However, recently, some studies have addressed tourism resilience in a broader range, primarily because of how tourism and hospitality has been affected by COVID-19. The pandemic had completely different characteristics from other disasters that affected tourism businesses previously—namely, its global range and long duration. When studying business recovery, it is relevant to investigate how managerial models and perceptions affected how T&H firms responded to the consequences of the pandemic. The purpose is to study how T&H firms' entrepreneurial orientation and managers' perception of the external environment, namely market recovery, relate to the actions taken during the pandemic. We conducted a cluster analysis to test our propositions considering two clustering variables: EO (Entrepreneurial Orientation) and MRP (Market Recovery Perception). Results suggest three types of T&H firms exist and that these opted for different recovery actions during the COVID-19 pandemic. Finally, our work presents a set of important theoretical and practical implications that can be useful to several stakeholders, namely academics and professionals.
Keywords: 650; Entrepreneurial orientation; tourism; hospitality; covid-19; recovery; environmental perception